2021
DOI: 10.1037/fam0000831
|View full text |Cite
|
Sign up to set email alerts
|

Chinese American children’s temperamental shyness and responses to peer victimization as moderated by maternal praise.

Abstract: Introduction. This study examined the relations between Chinese American children's temperamental shyness and their assertive and submissive responses to peer victimization.The mediating role of children's anxious-withdrawn behavior in the association between their temperamental shyness and responses to peer victimization in school settings was assessed, as well as the moderating effect of observed maternal praise. Method. Mothers of 153 Chinese American children (46.4% boys; Mage = 4.40 years, SDage = 0.79 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…There is some evidence suggesting that findings may be generalizable to at least some cultural groups, particularly if their children are evaluated by the dominant cultural norms (Carlo, Cheah, Conejo, & Cho, 2022). For example, similar to White American children, Asian immigrant children's temperamental shyness was associated with more anxious‐withdrawn behaviors, particularly if they received low praise from their mothers, and anxious‐withdrawn behavior, in turn, was associated with peer exclusion and passive responses to bullying (Gao et al., 2021), and decreased prosociality and leadership skills (Balkaya, Cheah, Yu, Hart, & Sun, 2018). Similarly, ‘anxious shyness’, reflecting an inability to attend group participation, was associated with peer rejection, whereas ‘regulated shyness’, reflecting more reserved and modest behaviors was not (Xu & Krieg, 2014).…”
Section: The Role Of Caregiving In the Relation Between Behavioral In...mentioning
confidence: 99%
“…There is some evidence suggesting that findings may be generalizable to at least some cultural groups, particularly if their children are evaluated by the dominant cultural norms (Carlo, Cheah, Conejo, & Cho, 2022). For example, similar to White American children, Asian immigrant children's temperamental shyness was associated with more anxious‐withdrawn behaviors, particularly if they received low praise from their mothers, and anxious‐withdrawn behavior, in turn, was associated with peer exclusion and passive responses to bullying (Gao et al., 2021), and decreased prosociality and leadership skills (Balkaya, Cheah, Yu, Hart, & Sun, 2018). Similarly, ‘anxious shyness’, reflecting an inability to attend group participation, was associated with peer rejection, whereas ‘regulated shyness’, reflecting more reserved and modest behaviors was not (Xu & Krieg, 2014).…”
Section: The Role Of Caregiving In the Relation Between Behavioral In...mentioning
confidence: 99%
“…Similar to their White American peers, Asian immigrant children's temperamental shyness has been found to be associated with more anxious-withdrawn behavior (Balkaya et al, 2018;Gao et al, 2021). Anxious withdrawn behavior, in turn, is associated with increased peer exclusion and more passive responses to bullying (Gao et al, 2021) and decreased prosocial behaviors and leadership skills (Balkaya et al, 2018) in Chinese immigrant children.…”
Section: Asian Immigrant Childrenmentioning
confidence: 96%
“…Similar to their White American peers, Asian immigrant children's temperamental shyness has been found to be associated with more anxious-withdrawn behavior (Balkaya et al, 2018;Gao et al, 2021). Anxious withdrawn behavior, in turn, is associated with increased peer exclusion and more passive responses to bullying (Gao et al, 2021) and decreased prosocial behaviors and leadership skills (Balkaya et al, 2018) in Chinese immigrant children. However, Asian immigrant parents' culturally emphasized socialization messages that encourage children to display humble and modest behaviors may convey their acceptance of children's shy dispositions and buffer against children's temperamental disposition and help shy children display less anxious behaviors and more positive socioemotional adjustment (Balkaya et al, 2018).…”
Section: Asian Immigrant Childrenmentioning
confidence: 96%
“…The common manifestation is that aggressive actions are carried out other than a rational way to deal with conflicts. Gao and his colleagues revealed the relationship between maternal praise, temporal shyness, and response type against peer victimization [18]. According to their research, children who have a temperamental shyness trait respond to peer victimization with less assertiveness and more submissiveness, which is mediated by anxiouswithdrawn behaviors [18].…”
Section: Shynessmentioning
confidence: 99%
“…Gao and his colleagues revealed the relationship between maternal praise, temporal shyness, and response type against peer victimization [18]. According to their research, children who have a temperamental shyness trait respond to peer victimization with less assertiveness and more submissiveness, which is mediated by anxiouswithdrawn behaviors [18]. It was also revealed that maternal praise serves as a moderator, alleviating the negative effects of temperamental shyness and decreasing children's submissive compromise to victimization [18].…”
Section: Shynessmentioning
confidence: 99%